Accessibility to Dental Prosthesis of Thai Aging Population in 2007 - Wongkongkathep, Sunee (Journal of Health Science of Thailand, 2017)
This study was aimed at reviewing how elderly people in Thailand access to dental prosthesis service. Primary data was derived from two major household surveys conducted by National Statistic Bureau in 2007; health and welfare survey, and economic and social status survey (n = 25,974 households and 69,679 individuals). Extrapolation to total population by weight was then calculated. Overall, 97.5 percent health insurance coverage was found among aging population, of which national health insurance scheme contributed 76.9 percent. Among them, dental health care utilization was only 8.2%. Extraction was the most common (56.1%) and community hospital was visited (46.5%). Considering dental prosthesis (16.6%), omit of health insurance scheme prevailed at 60% with high consultation to private service (49.3%). On the other hand, among those under their national health insurance, only 57.3-58.2 percent could access to dental prosthesis free of charge, compared to one-third of those better-off population in urban municipalities. That concluded obviously the inequity in accessibility to dental prosthesis among elderly people in Thailand.